Male and Couple Fertility Impairment due to HPV-DNA Sperm Infection: Update on Molecular Mechanism and Clinical Impact—Systematic Review. (25th March 2014) - Gizzo, Salvatore; Ferrari, Bruno; Noventa, Marco; Ferrari, Emanuele; Patrelli, Tito Silvio; Gangemi, Michele; Nardelli, Giovanni Battista
Abstract : Recent evidences identify Human Papillomavirus (HPV) sperm infection as a possible cause of male and couple infertility. It acts through different mechanisms at various steps of human conception and early gestational development. We performed a systematic review to assess the role of HPV semen infection on male and couple infertility. Analysis of available and eligible data does not permit us to fund clear evidences about clinical impact of HPV infection on fertility, although sperm parameters impairment is the most widely recognized effect. Regarding biomolecular implications, the available data are often conflicting. More studies are required to define the role of HPV sperm infection in clinical practice. The great majority of evidences are obtained by in vitro studies and this fact represents a limitation for the clinical management of HPVDNA sperm infection. Understanding the biological significance of HPV-DNA semen infection could permit us to explain most of the idiopathic male and couple infertility, leading to a better management of infertile men and a better timing for sperm banking storage before ART cycles.